The Influence of Investment Funds and Financial Statements on the Solvency Ratio at PT Bukit Asam Tbk from 2011 to 2021 - Ralia, Hagus; Diah Pasha, Novita Citra (Jurnal Indonesia Sosial Sains, 2026)
PT Bukit Asam Tbk is a state-owned mining and palm oil company listed on the IDX. However, it is uncertain whether its investment funds and financial statements comprising income statements, equity statements, and balance sheets have been properly audited and managed, particularly during periods of declining income. The purpose of this study is to examine the impact of investment funds and financial statements on the solvency ratio at PT Bukit Asam Tbk, both partially and simultaneously, during the period 2011 to 2021. This research was conducted at PT Bukit Asam Tbk; the data sourced from the financial reports published on the IDX. This study employed quantitative data, derived from secondary sources, and were processed using Eviews 10 over a timeframe of 2011–2021, comprising 11 annual observations. Based on the results, the t-test indicates that not all investment fund and financial statement variables have a significant effect on the solvency ratio. This implies that business management has been less effective in managing its investment funds. The F-test, however, indicates a significant combined effect on the company's solvency. This highlights the importance of effectively managing investment funds and financial reports in order to positively influence solvency.